Advertising Organizations and Publications : a Resource Guide. - Jones, Professor John Philip Philip (SAGE Publications, 2000)
John Philip Jones has compiled a comprehensive guide to the 77 key organizations and publications in the field of advertising and marketing communications. Entries are arranged alphabetically for easy access and include a thorough description of each organization's purpose, activity and contact information. The collection is balanced among industry trade organizations (American Association of Advertising Agencies), research organizations (Marketing Science Institute), academic organizations (American Academy of Advertising), and pro-social organizations (Partnership for a Drug-Free Americ.